Confessions of a rebel debutante : a cordial invitation - Fields, Anna, 1981- (New York : G.P. Putnam's Sons, 2010)
A fond, funny Southern-fried memoir about growing up a proper young lady ... or not. How does a North Carolina native go from being a tomboy with catfish guts on her overalls to becoming the next Scarlett O'Hara' Turns out, it's not so easy. Too smart, too tall, too fat, too different ... Anna Fields was a dud at debbing. From tea parties to teased hair to where to hide mini bottles of liquor inside poufy crinoline ballgowns, Anna reveals all-in a hilarious, behindthe-scenes glimpse into Deb Culture, where for a Southern belle, "the proof is in the pouf." Unless, of course, she rebels ..
Sugar and spice and-- well, mostly just sugar : a (wannabe) Scarlett is born -- Fake IDs and faker tans-- how Scarlett survives her first year of boarding school : tenth grade -- Scarlett faces the inquisition-- and becomes a rebel deb : eleventh grade -- How a rebel deb semi-steals a car and still lands on her feet : twelfth grade -- (I wish I were) Charlotte Simmons : a rebel deb goes to Brown -- From "dollywood" to Hollywood : a rebel deb goes to Los Angeles -- My momma says hummus looks like cat sick : a rebel deb finds her home in New York.
Keywords: Fields, Anna, -- 1981- -- Childhood and youth; Young women -- United States -- Biography; Teenage girls -- North Carolina -- Burlington -- Biography; High school students -- North Carolina -- Burlington -- Biography; Debutantes -- North Carolina -- Burlington -- Biography; Burlington (N.C.) -- Biography; Burlington (N.C.) -- Social life and customs; Los Angeles (Calif.) -- Biography; New York (N.Y.) -- Biography